2019
DOI: 10.1089/dia.2018.0401
|View full text |Cite
|
Sign up to set email alerts
|

Factory-Calibrated Continuous Glucose Monitoring: How and Why It Works, and the Dangers of Reuse Beyond Approved Duration of Wear

Abstract: Continuous glucose monitors (CGM) display real-time glucose values enabling greater glycemic awareness with reduced management burden. Factory-calibrated CGM systems allow for glycemic assessment without the pain and inconvenience of fingerstick glucose testing. Advances in sensor chemistry and CGM algorithms have enabled factory-calibrated systems to have greater accuracy than previous generations of CGM technology. Despite these advances many patients and providers are hesitant about the idea of removing fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 33 publications
1
18
0
2
Order By: Relevance
“…This is consistent with Faulds and colleagues' study, which reported that adults using 670G in the first 3 months calibrated their sensor 3.2 times/day and checked BG an average of 6.5 times/day . In an era when many individuals with type 1 diabetes are using factory calibrated CGM systems, requiring BG checks and sensor calibrations may be too high a burden for sustained use of HCL.…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with Faulds and colleagues' study, which reported that adults using 670G in the first 3 months calibrated their sensor 3.2 times/day and checked BG an average of 6.5 times/day . In an era when many individuals with type 1 diabetes are using factory calibrated CGM systems, requiring BG checks and sensor calibrations may be too high a burden for sustained use of HCL.…”
Section: Discussionsupporting
confidence: 88%
“…The receiver options vary by CGM type and may include a hand-held device, an insulin pump, or a mobile application on a smart phone or other device (i.e., apple watch, etc.). The CGM sensor is a glucose oxidase electrode, which generates an electrical current in the presence of glucose in the interstitial fluid and then converts that information into an estimated blood glucose value (Forlenza et al, 2019). As such, it is important to realize that CGM is not measuring blood glucose values directly, and it is not measuring capillary blood glucose levels, like SMBG.…”
Section: Overview Of Cgmmentioning
confidence: 99%
“…The most current Dexcom CGM (Dexcom G6) is factory calibrated, and therefore does not require the user to calibrate the sensor with SMBG values (Forlenza et al, 2019). The user can choose to calibrate, but generally, it is not recommended to calibrate with SMBG unless there is a reason to believe that the CGM is not reading accurately (i.e., symptoms do not match the CGM reading).…”
Section: Figure 1 Components Of Continuous Glucose Monitoringmentioning
confidence: 99%
“…Although the composition of CGMS has not changed significantly, the current CGMSs (Dexcom G6 ® and Abbott FreeStyle Libre) do not require calibration anymore. Since revolutionary change in CGMS is due to advance in sensor manufacturing, Dexcom G6 ® and Abbott FreeStyle Libre do not need in vivo calibration, thus reaching zero-finger pricking glucose monitoring [41]. As a result, diabetic patients can now relieve from painful, daily, routine finger-pricking calibration.…”
Section: Semi-implantalbe Cgms With Electrochemical Sensorsmentioning
confidence: 99%